मादले काँक्रो Madale cucumber (Genetics, Plant Breeding and Seed Science, 2025)
{The "Madale cucumber" variety, which is extensively cultivated in various parts of Parbat, Kaski, Baglung, and Myagdi districts of Gandaki Province, is believed to have originated in the Gandaki region. Known for its delicious taste, large size, long shelf life, resistance to many pests and diseases, and tolerance to heavy rain and waterlogging conditions, it is a popular indigenous variety that has been cultivated for generations. Due to these qualities and its cultural significance, it has been registered with the National Seed Board of Nepal for further conservation and promotion. In tests conducted in Maramche, Kaski during the year 2076/77 B.S. (2019/20 A.D.), Madale cucumber was found to be excellent in terms of taste, size, and yield. It starts flowering 70-80 days after transplantation and 40-50 kg of 3-5 kg-sized fruits can be harvested per plant in a growing season. Female to male flower ratio is 5-6: 1 and thousand seed weight is around 40 g. For long-term seed conservation, this variety has been assigned the accession number NGRC09585 and is preserved in the long-term storage unit of the National Gene Bank. Furthermore, for varietal promotion and source seed production, the Progressive Farmers' Group and the Annapurna Community Seed Bank located in Ward No. 3 of Annapurna Rural Municipality, Kaski, have been actively working on its cultivation and development. Given its adaptability to local climates, expanding the cultivation of Madale cucumber to other districts within Gandaki and neighbouring provinces is expected to boost cucumber production and contribute to the household economy of the farmers.}